PELATIHAN PEMBUATAN WEBSITE SEBAGAI PENUNJANG PROSES PEMBELAJARAN UNTUK GURU DI SD N 1 KARANGNOM KLATEN - Wuryandari, Aryati; Muryanto; Hartono, Fajar Budi; Prasetyo, Hendro Joko; Kusuma, Dito Anggit; Meutifa, Ellis Cindy; Kristanto, Yepta Ferdi (LPPM Universitas Widya Dharma Klaten, 2026)
The development of education in Indonesia demands a transformation in the curriculum and the use of technology to improve the quality of learning. A curriculum that is adaptive to current developments needs to be supported by information technology to make the teaching and learning process more effective and inclusive. Websites are one technology that plays a crucial role as a learning medium, a means of communication, and a provider of information for schools, teachers, students, and parents. However, limited teacher competency in website creation remains a barrier, primarily due to differences in expertise. This problem is also faced by SDN 1 Karanganom Klaten, where the majority of teachers do not yet have the skills to develop learning websites. As a solution, Widya Dharma University Klaten, in collaboration with SDN 1 Karanganom, conducted community service activities in the form of website creation training to support the learning process. This activity aims to improve teacher competency in website utilization and strengthen the synergy between universities and schools in supporting the improvement of educational quality.